Peran Lembaga Keuangan Mikro Syariah dalam Pengentasan Kemiskinan di Indonesia - Ayu Fitriana; Muna Sofiana; Siti Nahdiatun Nisa’; Satria Putra Arsibal; Novi Khoiriawati (Universitas 45 Surabaya, 2024)
The role of Micro Sharia Financial Institutions in overcoming poverty in Indonesia is needed through the financial services that have been provided. Indonesia has been intensively trying to overcome poverty because one of the main goals of national development is to reduce and even eliminate poverty. In March 2023 the number of poor people in Indonesia has decreased to 25.90 million people. The purpose of this research is to describe the role of Sharia Microfinance Institutions in alleviating poverty in Indonesia. This research uses a descriptive qualitative approach research method with secondary data obtained from books, journals, and data sources related to the study under study. The results of this study found that Micro Sharia Financial Institutions in the form of BMT (Baitul Maal wat Tamwil) have a very large role in poverty alleviation in Indonesia. Capital from BMT will be channeled to small communities so as to open up opportunities in creating jobs and alleviating poverty.